HEALTH SECURITY OF THE BRAZILIAN BORDERS AND TRANSNATIONAL THREATS TO NATIONAL AGRICULTURAL PRODUCTION - Pinho de Andrade Lima, José Roberto (2023)
Environmental and health risks are the most worrying in terms of economic impact and probability of occurrence. One of the most urgent threats to national and global security in the twenty-first century is climate change. Given that Brazil is the world's largest producer of animal protein and a major exporter, any disease affecting cattle, pigs, and poultry will represent a catastrophe with huge economic, social, and political repercussions. This article is the result of an exploratory, descriptive and applied study in a qualitative way, using bibliographic and documentary research techniques. The objective was to analyze existing capacities in Brazil for the monitoring and confrontation of major agricultural and livestock health emergencies. There is a need to improve the governance of the National Disaster Response System and to promote the doctrinal and operational integration of Civil Defense as one of the main actors in crisis management, such as the Ministry of Agriculture, Health and Defense. The creation of an independent agency specializing in the monitoring and management of the health emergency response within the framework of the Center for Disease Control (CDC) in the United States, Europe, Africa and China can be an important strategy to optimize resources and develop resilience.